Analysis of artisanal fisheries in two reservoirs of the upper Paraná River basin (Southeastern Brazil) - Novaes, José Luís Costa; Carvalho, Edmir Daniel [UNESP] (FapUNIFESP (SciELO), 2013)
We compared the artisanal fisheries, in terms of catch strategies, productivity, and gross per capita income, at two reservoirs: The Barra Bonita (an eutrophic reservoir with some introduced species), and the Jurumirim (an oligotrophic reservoir, with no introduced species). Published data and structured interviews with fishers were used to evaluate fishing activity, fish biomass, and the financial performance of the fisheries. In the Barra Bonita Reservoir we analysed data from 745 fishing trips, from which 86,691.9 kg of fish were landed, with a mean CPUE of 62.4 kg/fisher-1 day-1. The main type of fish caught was tilapia (71,513.5 kg; CPUE of 51.5 kg/fisher-1 day-1), which constituted 82.5% of the biomass caught. In the Jurumirim Reservoir, we analysed data from 2,401 fishing trips, from which 25,093.6 kg of fish were landed, with a mean CPUE of 10.4 kg/fisher-1 day-1. The main type of fish caught was traíra (6,158.6 kg; CPUE of 2.6 kg/fisher-1 day-1), which constituted 24.5% of the biomass caught. Ordination analysis (PCA) indicated that there was a difference in composition between the fishing reservoirs and ANCOVA showed that there was a significant difference in fish production between the reservoirs. A Student's t-test showed that fishers in the Barra Bonita Reservoir had a significantly higher gross per capita income than those from the Jurumirim Reservoir. Although the Barra Bonita Reservoir has a higher fish production and the fishers earn a higher gross per capita income, we recommend the Jurumirim Reservoir as a model for artisanal fishery management because fishing activity in this reservoir is viable in the long term and such a model would promote conservation and sustainability. This contrasts with the Barra Bonita Reservoir, in which the fishery is not viable in the long term, due to environmental problems caused by artificial eutrophication and the introduction of alien species. It is also noted that in many countries, management of fisheries based on exotic species has not been viable in the long term. © 2013 Sociedade Brasileira de Ictiologia.
Keywords: Barra Bonita Reservoir; Fish; Jurumirim Reservoir; Paranapanema River; Tietê River